Mucuna pruriens for Parkinson's disease: Low-cost preparation method, laboratory measures and pharmacokinetics profile - Cassani, E.; Cilia, R.; Laguna, J.; Barichella, M.; Contin, M.; Cereda, E.; Isaias, I.U.; Sparvoli, F.; Akpalu, A.; Budu, K.O.; Scarpa, M.T.; Pezzoli, G. (Journal of the Neurological Sciences, 2016)
Background Parkinson's disease (PD) is a progressive neurological condition. Levodopa (LD) is the gold standard therapy for PD patients. Most PD patients in low-income areas cannot afford long-term daily Levodopa therapy. The aim of our study was to investigate if Mucuna pruriens (MP), a legume with high LD content that grows in tropical regions worldwide, might be potential alternative for poor PD patients. Methods We analyzed 25 samples of MP from Africa, Latin America and Asia. We measured the content in LD in various MP preparations (dried, roasted, boiled). LD pharmacokinetics and motor response were recorded in four PD patients, comparing MP vs. LD + Dopa-Decarboxylase Inhibitor (DDCI) formulations. Results Median LD concentration in dried MP seeds was 5.29%; similar results were obtained in roasted powder samples (5.3%), while boiling reduced LD content up to 70%. Compared to LD + DDCI, MP extract at similar LD dose provided less clinical benefit, with a 3.5-fold lower median AUC. Conclusion Considering the lack of a DDCI, MP therapy may provide clinical benefit only when content of LD is at least 3.5-fold the standard LD + DDCI. If long-term MP proves to be safe and effective in controlled clinical trials, it may be a sustainable alternative therapy for PD in low-income countries. © 2016 The Authors.
Keywords: Levodopa; Mucuna pruriens; Parkinson's disease